LEGAL PROTECTION FOR REGISTERED TRADEMARK OWNERS AMONG MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) - Hendri Saputra Manalu; Rahmadany; Anto Mutriady; Deded Syahputra; Janner Damanik; Tengku Shafa Fitri Zahra (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
Micro, small, and medium enterprises (MSMEs) produce fashion, culinary, and other creative products that require clear legal protection, particularly for trademarks. This article examines the importance of trademark registration for MSME actors and the legal protection available to registered trademark owners in Indonesia. The discussion is based on relevant statutory provisions, literature, and data concerning trademarks and MSMEs. The analysis shows that trademarks function as distinguishing signs, product and business identities, and instruments that strengthen consumer trust. However, digital business development also creates opportunities for unauthorized use, piracy, and even prior registration by irresponsible parties, which may reduce market prices, consumer confidence, and sales turnover. Registration with the Directorate General of Intellectual Property provides legal certainty, exclusive rights, authentic evidence of ownership, a basis for rejecting similar applications, and a basis for preventing unauthorized use. Registered trademarks are protected for ten years from the filing date and may be renewed. Therefore, early trademark registration is a preventive measure that enables MSMEs to avoid disputes, strengthen their bargaining position, and expand business opportunities.